Psoriasis Gutata - Laporan Kasus - Dotulong, Julieta D. P.; Korompis, Charly M. M.; Pandaleke, Herry E. J. (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Guttate psoriasis (GP) is a variant of psoriasis with typical drop-shaped lesions sized 0.5-1 cm in diameter, localized especially in the upper part of the body and proximal extremities. It usually occurs in young adult. We reported a female,11 years old, with red, itchy, and scaly patches distributed nearly all over the body. There was a history of sore throat. Dermatologic status showed multiple erythematous plaques which were miliar to numular, discrete, and were covered with layered silvery white scales. The Auspitz sign, wax spot phenomenon, and ASTO were positive. The histopathologic examination showed para-keratosis and Munro microabcesses. The patient treated with topical steroid for 4 weeks made improvement. Conclusion: In this case, diagnosis of guttate psoriasis was based on anamnesis, examination, and supporting examinations. Streptococcal infection was suspected as the trigger factor due to the positive ASTO examination. Topical steroid as the first line therapy for mild to moderate psoriasis made great improvement.Keywords: guttate psoriasis, streptococcal infectionAbstrak: Psoriasis gutata (PG) merupakan varian dari psoriasis. Gambaran khasnya seperti tetesan air dengan diameter 0,5-1 cm, di badan bagian atas dan ekstremitas proksimal. Sering terjadi pada dewasa muda. Kami melaporkan kasus seorang perempuan berusia 11 tahun dengan bercak merah meninggi, bersisik, disertai gatal pada hampir seluruh tubuh. Riwayat nyeri menelan positif. Riwayat pengobatan sebelumnya disangkal. Status dermatologis ditemukan plak eritem, multipel, miliar-numular, diskret, ditutupi skuama berlapis warna putih keperakan. Pemeriksaan tanda Auspitz, fenomena bercak lilin, dan ASTO positif. Pada pemeriksaan histopatologik didapatkan adanya parakeratosis dan mikroabses Munro. Terapi steroid topikal potensi tinggi selama 4 minggu menunjukkan perbaikan. Simpulan: Pada kasus ini diagnosis psoriasis gutata ditegakkan berdasarkan anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang yang khas. Infeksi streptokokus diduga sebagai faktor pencetus berdasarkan hasil pemeriksaan ASTO. Terapi steroid topikal merupakan lini pertama untuk psoriasis ringan sampai sedang memperlihatkan perbaikan yang nyata.Kata kunci: psoriasis gutata, infeksi streptokokus